2015
DOI: 10.3906/bot-1506-15
|View full text |Cite
|
Sign up to set email alerts
|

Activated expression of EsHD1 enhances drought tolerance in tobacco plants via mitigation of reactive oxygen species-mediated membrane damage

Abstract: It is well documented that the homeodomain-leucine zipper (HD-Zip) transcription factors play diverse roles during plant growth and development. The Class I HD-Zip genes are shown to be involved in the regulation of abiotic stress responses and tolerance. Herein, a novel Class I HD-Zip gene, EsHD1, was isolated from Eutrema salsugineum, and an investigation was performed of its physiological functions in response to drought stress. The analyses of gene expression profiles revealed that the EsHD1 transcripts qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…The photosynthetic rates (Pn) of both the control and inoculated plants markedly dropped because of drought stress, but the value of Pn was considerably higher in the inoculated plants than in the control plants ( Figure 6 a). The chlorophyll content has been taken as a typical indicator that evaluates the ability of plants to tolerate abiotic stress [ 28 ]. Our data showed that the amount of chlorophyll displayed evident alterations with a gradual decrease accompanied by the time-delay of drought treatments ( Figure 6 b).…”
Section: Resultsmentioning
confidence: 99%
“…The photosynthetic rates (Pn) of both the control and inoculated plants markedly dropped because of drought stress, but the value of Pn was considerably higher in the inoculated plants than in the control plants ( Figure 6 a). The chlorophyll content has been taken as a typical indicator that evaluates the ability of plants to tolerate abiotic stress [ 28 ]. Our data showed that the amount of chlorophyll displayed evident alterations with a gradual decrease accompanied by the time-delay of drought treatments ( Figure 6 b).…”
Section: Resultsmentioning
confidence: 99%